ANALISA PENGARUH KEMIRINGAN SUDUT SCREW EXTRUDER PADA PROSES PEMBUATAN FILAMENT 3D PRINTER PADA MESIN EKSTRUSI SINGLE SCREW - Rasid, Muhammad Rasid; Suparjo, Suparjo; Tafrant, Dodi; Homzah, Ozkar F.; Maâ€™arif, Syamsul (Politeknik Negeri Sriwijaya, Indonesia, 2022)
The purpose of this research is to calculate the effect of the screw extruder angle on the results of 3-dimensional printer filaments that are printed using a single screw extrusion machine. The machine parameters used in this study were: pull speed 16 rpm, extrusion speed 28 rpm, extrusion mold diameter of 2 mm, and temperature of 180oC. The material used is recycled HDPE plastic. While the tilt angle of the screw in the research conducted by providing 5 variants of the angle of inclination (0o, 10o, 15o, 20o, 25o) where the diameter of the screw shaft used is the same. Data analysis was carried out using a simple linear regression method. Where the results obtained were: 1) the smallest filament diameter was 0.9 mm when using a screw with an angle of 0o, and 2) the highest diameter was 1.86 mm when using a screw with an angle of 25Âº. The conclusion obtained is that the tilt angle of the helical screw affects the results of recycled HDPE plastic extrusions, where the effect of the screw angle tilt is directly proportional to the filament diameter. In other words, with the addition of the tilt angle of the screw, the diameter of the resulting filament will also increase. In addition, based on the results of measuring the diameter of the filament, the conclusion that can be drawn is that with the increase in the diameter of the extrusion result, the outflow obtained will also be greater.